A versatile approach to fabricate modulated micro-/nanostructures by electrohydrodynamic structuring on prepatterned polymer. (23rd December 2016) - Tian, Hongmiao; Shao, Jinyou; Chen, Xiaoliang; Wang, Li; Ding, Yucheng
Abstract: Micro-/nanostructures fabricated on functional polymers from physical principles can be highly desirable for polymer devices, owing to the physical integrity of the generated structure, the process economy and their environmentally friendly quality. However, current fabricating approaches can only duplicate a specific structure, or may require a complex technological procedure for the fabrication, i.e. for the fabrication of modulated micro-/nanostructures on polymer films on the basis of the physical principles, a versatile yet simple procedure is lacking. In this paper, electrohydrodynamic structuring on prepatterned polymer (ESPP) based on the electrohydrodynamic behavior of fluidic polymers in an electric field is proposed for the fabrication of a modulated structure on a functional polymer. For this purpose, a voltage is applied between a flat template and a flat substrate, sandwiching a prepatterned polymer and an air gap, resulting in a non-uniform upward pull on the polymer. This leads to a deformation of the polymer resulting in a structure corresponding to the initial morphology. This study explores the capability of ESPP in duplicating modulated structures by manipulating the electric field (which is also influenced by process parameters involving voltage and air gap length) from the perspective of theoretical analysis and experimental tests, which categorize the relationship between electrohydrodynamic pressure and surface tension into two regimes: one consisting of equilibrium modulation for convex structures potentially used as microlens arrays, and another comprising non-equilibrium modulation for high aspect ratio structures and potentially applicable to dry adhesives, superhydrophobic surfaces, etc. Furthermore, a criterion is proposed to distinguish between the two aforementioned regimes.